Tailored bimetallic Zn/Ni and Zn/Ag MCM-41 photocatalysts for enhanced visible-light photocatalytic tetracycline degradation - Mohammed Ahmed Wahba; Rabab K. Khaled; Magdah Dawy (Scientific Reports)
Abstract Novel bimetallic-doped-MCM-41(Mobil Composition of Matter No. 41) (Zn/Ni-MCM-41 (ZNM)) and (Zn/Ag-MCM-41 (ZAM)) catalysts were synthesized and characterized for their structural, textural, morphological, and optical properties. XRD analysis confirmed metal incorporation into the MCM-41 framework, while N2 adsorption-desorption isotherms indicated a decrease in specific surface area (1210 in pure MCM-41 to 722.86 and 700.36 m2/g for ZNM and ZAM, respectively) due to partial pore filling. TEM images verified this finding. Boosted absorption extending into the visible light region was detected in the metal incorporated (ZNM and ZAM) samples with additional band gaps, related to transitions in Zn2+, Ag+ and Ni2+ ions. Photoluminescence studies revealed efficient charge carrier separation in ZNM and ZAM. Both catalysts exhibited superior tetracycline (TC) removal from aqueous solution with efficiency (95.59% and 95.30% within one hour for ZNM and ZAM, respectively) with pronouncing visible light photocatalytic capability compared to pure MCM-41. The degradation process followed pseudo-first-order kinetics. The enhanced photocatalytic activity of ZNM and ZAM is attributed to the synergistic effects of metal incorporation, increased light absorption, and efficient charge carrier dynamics. Additionally, a possible photocatalytic mechanism for degradation of TC over ZNM and ZAM has been proposed and involvement of superoxide radicals (O2 •−) and holes (h+) as reactive species is elucidated by radical trapping experiments. A distinct pH-dependent trend was observed in TC degradation efficiency using the ZAM photocatalyst. The efficiency gradually increased with increasing pH until reaching a maximum at pH 7, followed by a decline at higher pH values. These results demonstrate the potential of ZNM and ZAM as promising materials for removal of tetracycline antibiotic from water.